A Holistic Management 48 Years Old Woman With Vertigo Through The Family Medicine Approach - Wardani, Hanifa Nurusita; Sibuea, Sahab (CV. Jasa Sukses Abadi, 2023)
Vertigo is a false perception of a person's movements or the surrounding environment. The prevalence of vertigo in Indonesia in 2018 is 50% of those aged 40-50 years and is the third most common complaint complained of by patients who come to general practice after headaches and strokes. This research aims to implementing a holistic and comprehensive approach of a family doctor according to the problems experienced by patients and patient management based on evidence based medicine, patient centered, family oriented and community oriented. Primary data was obtained through autoanamnesis, physical examination and home visits. Secondary data was obtained from the patient's medical record. Assessment based on a holistic diagnosis from the beginning of the process and the final study qualitatively and quantitatively. In results patient Mrs. S, 48 years old, came to the primary care with dizziness, nausea, vomiting, and cold sweats. On physical examination, there was the results of the Dix Hallpike neurological test, nystagmus, Romberg, tendem gait, and past pointing test were positive. Fukuda stepping test result was negative. The patient has curative treatment patterns, lack of knowledge about the disease. The external risk aspects of the patient are the lack of family knowledge about the patient's illness and curative family treatment patterns. Furthermore, holistic management of patients and families through poster and power point in the form of information about the diseases suffered by patients, exercise that can be done by the patient. At the time of evaluation, the patient had no symptoms anymore. Holistic management can increase knowledge and change the patient’s behavior. The role and support of the family are needed in the treatment of the patient.